Correlation of a scanning laser derived oedema index and visual function following grid laser treatment for diabetic macular oedema. Issue 4 (1st April 2003) - Hudson, C; Flanagan, J G; Turner, G S; Chen, H C; Young, L B; McLeod, D
Abstract : Aim: To correlate change of an oedema index derived by scanning laser tomography with change of visual function in patients undergoing grid laser photocoagulation for clinically significant diabetic macular oedema (DMO). Methods: The sample comprised 24 diabetic patients with retinal thickening within 500 μm of the fovea. Inclusion criteria included a logMAR visual acuity of 0.25, or better. Patients were assessed twice before a single session of grid laser treatment and within 1 week of, and at 1, 2, 4, and 12 weeks after, treatment. At each visit, patients underwent logMAR visual acuity, conventional and short wavelength automated perimetry (SWAP), and scanning laser tomography. Each visual function parameter was correlated with the mean oedema index. The mean oedema index represented the z-profile signal width divided by the maximum reflectance intensity (arbitrary units). A Pearson correlation coefficient (Bonferroni corrected) was undertaken on the data set of each patient. Results: 13 patients exhibited significant correlation of the mean oedema index and at least one measure of visual function for the 10° × 10° scan field while 10 patients correlated for the 20° × 20° scan field. Seven patients demonstrated correlation for both scan fields. Laser photocoagulation typically resulted in an immediate loss of perimetric sensitivity whereas the oedema index changed over a period of weeks. Localised oedema did not impact upon visual acuity or letter contrast sensitivity when situated extrafoveally. Conclusions: Correlation of change of the oedema index and of visual function following grid laser photocoagulation was not found in all patients. An absence of correlation can be explained by the localised distribution of DMO in this sample of patients, as well as by differences in the time course of change of the oedema index and visual function. The study has objectively documented change in the magnitude and distribution of DMO following grid laser treatment and has established the relation of this change to the change in visual function.